Analysis of Islamic Religious Education (PAI) Teachers' Strategies to Prevent Bullying Through Artificial Intelligence at SMP 1 Palu - Nurhayati Nurhayati; Humairah Mahmud Abdullah; Askar Askar; Jihan Jihan; Nasrul Nasrul (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This research is motivated by the increasing number of bullying cases in schools, which negatively impact the psychological and academic development of students. Islamic Religious Education (PAI) teachers play a strategic role in shaping students' character and morals through a religious values approach. The purpose of this study is to analyze the strategies implemented by PAI teachers in preventing bullying at SMP 1 Palu by utilizing artificial intelligence (AI) technology as a detection tool and learning approach. This study used a qualitative method with a case study approach. Data were obtained through in-depth interviews, observations, and documentation of PAI teachers and students. The results show that PAI teachers utilize AI-based platforms such as educational chatbots and behavior monitoring systems to detect potential bullying and convey religious values interactively. This strategy has been proven to increase students' awareness of the importance of tolerance, empathy, and noble character. The conclusion of this study is that the integration of artificial intelligence technology with religious education provides an innovative and effective approach to preventing bullying in schools.